Global test for covariate significance in quantile regression - Mrkvička, Tomáš; Konstantinou, Konstantinos; Kuronen, Mikko; Myllymäki, Mari (Springer Nature, 2026)
Quantile regression is used to study effects of covariates on a particular quantile of the data distribution. Here we are interested in the question whether a covariate has any effect on the entire data distribution, i.e., on any of the quantiles. To this end, we treat all the quantiles simultaneously and consider global tests for the existence of the covariate effect in the presence of nuisance covariates. This global test for covariate significance in quantile regression can be used as the extension of linear regression or as the extension of distribution comparison in the sense of Kolmogorov-Smirnov test or as the extension of partial correlation. The proposed method is based on pointwise coefficients, permutations and global envelope tests. The global envelope test serves as the multiple test adjustment procedure controlling the family-wise error rate and provides the graphical interpretation which automatically shows the quantiles or the levels of categorical covariate responsible for the rejection. The Freedman-Lane permutation strategy showed liberality of the test for extreme quantiles, therefore we propose four alternatives that work well even for extreme quantiles and are suitable in different conditions. One of the strategies is suitable in a general situation, while others under more specific conditions. We show asymptotic exactness of the proposed permutation procedures and present a simulation study to inspect the performance of these strategies, and we apply the chosen strategies to two data examples.
Keywords: distribution comparison; global envelope test; multiple comparison problem; permutation test; significance testing; simultaneous testing